Cryoprotectants and their changes in cabbage aphid, Brevicoryne brassicae (Hem.: Aphididae) - S. Moharramipour; F. Saeidi; M. Barzegar (نامه انجمن حشره‌شناسی ایران, 2013)
Cabbage aphid, Brevicoryne brassicae (L.), is an important pest of cabbage, especially ornamental cabbages, due to its voracity and population build-up on these plants in wintertime. The cryoprotectants of B. brassicae and their changes were investigated during the cold seasons. Adult aphids were collected monthly on ornamental cabbages from October 2008 through May 2009. The amount of sugars and polyols were measured by high performance liquid chromatography (HPLC) and the amount of glycogen was spectrophotometrically determined. The identified compounds were as follows: glucose, mannitol, myo-inositol and trehalose. Mannitol, myo-inositol and trehalose were significantly correlated with average temperature. The total amount of these compounds increased from the lowest amount (11.90 ± 3.07 µmol/g f.w.) in October to its highest (55.8 ± 8.83 µmol/g f.w.) in the coldest month, January. There appears that these three compounds, especially mannitol, play important roles in enhancing cold tolerance of B. brassicae during cold seasons. The amount of glycogen showed no significant differences during those months and varied from 4.8 ± 0.58 mg/g f.w. in October to 3.3 ± 0.98 mg/g f.w. in December. There was no significant correlation between glycogen and the cryoprotectants.